Variations in susceptibility to the effects of trypanosmiasis in East African Zebu cattle - Rowlands, G.J.; D'Ieteren, G.D.M.; Authié, Edith; Leak, S.G.A.; Mulatu, W.; Nagda, S.M. (International Laboratory for Research on Animal Diseases, 1994)
Bovine trypanosomiasis is prevalent in southwest Ethiopia infested with tsetse flies. Since 1986, East African Zebu cattle raised under trypanosomiasis risk in the Ghibe Valley of southwest Ethiopia have been studied to investigate the effects of trypanosmiasis on health and productivity. Approximately 840 ear-tagged East African Zebu cattle from nine village herds in the Ghibe Valley, southwest Ethiopia, have been weighed and sampled monthly since March 1986. These cattle were of varying ages including calves and mature cattle. Blood samples were collected for the estimation of packed blood cell volume (PCV) and for the detection of trypanosomes using the darkground/phase contrast buffy coat technique. Animals with a PCV below 26 percent and detected parasitaemic, or animals showing clinical signs of trypanosomiasis, were treated with diminazene aceturate at 3.5 mg/kg bodyweight. 87 percent of all animals found parasitaemic during 1986 to 1991 had a PCV < 26 percent and were treated. 10 percent of treatments were administered to animals which showed clinical signs but which were not detected parasitaemic. Adult animals were treated on average three times a year. Effect of parasitaemia on productivity, associations between PCV and productivity, and offspring-dam regressions are discussed.